Theoretical insight of nitric oxide adsorption on neutral and charged Pd-n (n=1-5) clusters - Begum, Pakiza; Gogoi, Pranjal; Mishra, Bhupesh Kumar; Deka, Ramesh Chandra (International Journal of Quantum Chemistry, 2015)
Density functional theory (DFT) calculations within the framework of generalized gradient approximation have been used to systematically investigate the adsorption of nitric oxide (NO) molecule on neutral, cationic, and anionic Pd-n (n=1-5) clusters. NO coordinate to one Pd atom of the cluster by the end-on mode, where the tilted end-on structure is more favorable due to the additional electron in the * orbital. On the contrary, in the neutral and cationic Pd-2 system, NO coordinates to the bridge site of cluster preferably by the side-on mode. Charge transfer between Pd clusters and NO molecule and the corresponding weakening of NO bond is an essential factor for the adsorption. The NO stretching frequency follow the order of cationic>neutral>anionic. Binding energy of NO on anionic clusters is found to be greater than those of neutral and cationic clusters. (c) 2015 Wiley Periodicals, Inc.
Keywords: Density functional theory; electronic property; geometric configuration; NO adsorption; small palladium cluster

Controlling and stabilization of Ru nanoparticles by tuning the nitrogen content of the support for enhanced H-2 production through aqueous-phase reforming of glycerol - Gogoi, Pranjal; Kanna, Narsimharao; Begum, Pakiza; Deka, Ramesh C.; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (ACS Catalysis, 2020)
The stable activity of catalysts is an important issue in catalysis, particularly aqueous-phase reforming (APR) of renewable oxygenates, of biomass origin, to get H-2. Sintering of metal nanoparticles on supports affects catalyst stability. To alleviate this problem, a series of highly stable Ru-supported catalysts with controlled metal nanoparticle sizes have been prepared via the easy incipient wetness impregnation method. These catalysts were used for APR of glycerol to produce H-2. Nitrogen-doped mesoporous carbons (NMCs) were utlized as supports and found to have a strong influence on the catalytic performance of the catalysts. Incorporation of nitrogen in the carbon framework significantly enhanced the catalytic activity compared to Ru catalysts on nitrogen-free supports. Notably, the catalyst (5 wt % Ru-NMC-3) with optimal N content (10.9 wt %) demonstrated improved stability and H-2 selectivity, which are better than those of many state-of-the-art catalysts. Nitrogen in the carbon framework has a dual relationship with the activity of the catalyst: (i) it creates basic environment over the catalysts support and (ii) it acts as an anchoring site for metal nanoparticles. Anchoring of metal nanoparticles has helped to curb their sintering, thus leading to better stability of the catalysts under APR reaction conditions. Various characterization techniques were employed to understand the nature of active catalytic sites responsible for higher H-2 production while minimizing CO formation. In situ CO-FTIR studies showed that the higher catalytic activity of 5 wt % Ru-NMC-3 catalyst was attributed to the enhanced WGS activity over this catalyst. Density functional theory calculations were performed to understand the stabilization of metal nanoparticles by different types of N present on the support and provide insights into the prefered sites of glycerol adsorption on the NMC support. Since S wt % Ru-NMC-3 was the relatively best catalyst, it was selected for the preparation of bimetallic catalysts. Accordingly, addition of Pt to this system helped to increase the stability of the catalyst. This bimetallic catalyst may, therefore, find application for wide use in APR of biomass oxygenates.
Keywords: aqueous-phase reforming; Glycerol; H-2 production; Ru/NMC catalyst; synergistic effect